Perbedaan Karakteristik Ibu pada Anak Yang Mengalami Anemia dan Tidak Anemia di SD Negeri Banyuanyar III Kota Surakarta - Astuti, Niken Dwi, Ir. Listyani Hidayati, M.Kes, Fitriana Mustikaningrum, S.Gz, M.Sc (2013)
Introduction : The nutrition evaluation held in 2009 showed that 54,7% of elementary school students in Surakarta suffered from anemia. Data taken from Banyuanyar public health all students illustrated that have low hemoglobin (Hb) which is 20,7%. Objective : The aims of study is to gate the differences between who mother's characteristics (educational background, occupation, income and knowledge about nutrition) on children suffering anemia and without anemia at SD Negeri Banyuanyar III, Surakarta. Research methodology : This research is an observational with cross sectional design. The subjects of research are 265 from mothers student of elementary school grade I, II, III, IV, V and VI at SD Negeri Banyuanyar III, Surakarta. Data were collected by interview and questionnaire to figure out the mothers' knowledge about nutrition. Mann Whitney, Chi square, and independent t-test was used to analysed statistic. Result : Statistical analysis shows that there is no significant differences between educational background of mothers of children with anemia and without anemia (p=0.654). There is addition is no significant difference between occupation mothers of children with anemia and without anemia (p=0.834). There is addition is no significant difference between income of mothers of children with anemia and without (p=0.944). There is addition is no significant difference between knowledge about nutrition of mothers of children with anemia and without anemia (p=0.944). Conclusion : Overall, there are no differences between mother's characteristics consisting of educational background, occupation, income and knowldge about nutrition on children with anemia and without anemia at SD Negeri Banyuanyar III, Surakarta .